Biomass production and N fixation of five Mucuna pruriens varieties and their effect on maize yields in the forest zone of Cameroon - Hauser, S.; Nolte, C. (Wiley, 2002)
Mucuna has been tested intensively in past years as green manure for intensive maize production in West Africa. However, information is missing about the yield effect of different existing mucuna varieties. Five Mucuna pruriens varieties were grown for 40 weeks followed by sole maize (Zea mays L.) in order to determine differences in biomass production, nitrogen fixation, and effects on maize yield. Mucuna varieties differed in length of growing period, total biomass production (5.9—8.8 Mg ha—1), seed production (0.65—1.3 Mg ha—1), nitrogen (N) uptake (147—222 kg ha—1), N fixation (87—171 kg ha—1), and the amount of N retained in residues (138—218 kg ha—1). The grain yield of maize grown immediately after the short mucuna fallow was significantly higher after mucuna vars. jaspaeda (4.60 Mg ha—1), utilis (3.49 Mg ha—1), and cochinchinensis (3.44 Mg ha—1), compared with a non‐fertilized control (1.93 Mg ha—1) which had a maize crop and vegetation regrowth before. After mucuna vars. ghana and veracruz, 2.90 and 2.65 Mg ha—1 of maize grain were produced, respectively. No significant correlation between mucuna biomass and its N uptake and maize grain yield was found, whereas maize stover yield showed a significant positive correlation. Application of 30, 60, and 90 kg ha—1 N as <?tw=98%>urea on sub‐plots of the control yielded 2.20, 3.19, and 3.46 Mg ha—1 <?tw>of maize grain in the first year. Only the difference between 0 and 90 kg ha—1 N was significant. Fertilizer N equivalent values for mucuna varieties ranged from 41 to 148 kg ha—1. The yield advantage of vars. jaspaeda, utilis, and cochinchinensis versus the control without N fertilizer application was confirmed in the following year, with no significant difference in maize grain yield between mucuna and the control with N fertilizer application.